Phytochemical and Biological Studies on Bark Extract of Aporosa wallichii Hook.f. (Dhaka University Journal of Pharmaceutical Sciences, 2020)
The ethyl acetate extract of bark of Aporosa wallichii Hook.f. was extensively investigated for the chemical characterization of secondary metabolites and for biological activities. After repeated chromatographic separation and purification, two compounds were elucidated as a phenolic compound ferulic acid (1) and an uncommon triterpene glut-5(6)-en-3β-ol (2) from the ethyl acetate extract of barks of A. wallichii by using high field NMR analyses. This is the first report of isolation of both compounds from this plant species. No significant antimicrobial activity was observed for any fraction after Kupchan partitioning of the extract. During the antioxidant activity assay, the ethyl acetate soluble fraction of A. wallichii demonstrated significant DPPH radical scavenging capacity with an IC50 value of 1.25 μg/mL. The other fractions viz. petroleum ether, aqueous and chloroform soluble fractions exhibited moderate, mild, and weak activity respectively. The petroleum ether soluble fraction demonstrated maximum thrombolytic property (51.33%) which was similar to that of standard streptokinase (66.81%).Dhaka Univ. J. Pharm. Sci. 19(2): 139-143, 2020 (December)